Complete Mitochondrial DNA Sequences of Saccostrea Mordax and Saccostrea Cucullata: Genome Organization and Phylogeny Analysis - Kinaro, Zachary Omambia (Informa Health Care, 2015)
Classified in the phylum mollusks, oysters are bivalves which are found in estuaries and coastalzones. Because of their plastic shell, mitochondrial DNA analysis of this species becomes an interesting field, necessary to investigate their phylogenetic and evolution of relations. In our study, two oyster species: Saccostrea mordaxand Saccostrea cucullata from Indian Ocean(Madagascar) were investigated. The complete sequence of Saccostrea mordax (16 512 bp) and Saccostrea cucullata (16 396 bp) were described and determined, with their mitogenomes deposited in the Gen Bank with accession number KP769562 and KP967577 respectively. Both mitochondrial genome sequences contained 12 protein-coding genes, 23 tRNAs, and two rRNAs, all encoded in the same heavy strand. High levels of similarity in the gene arrangement of the two Saccostrea species were evident. The phylogenetic analysis shows a closer relationship between the two Saccostrea species and confirms the strong relationship within Saccostrea, Crassostrea and Ostrea genus in taxonomy of Ostreidae family.
Keywords: Evolution; Mitochondrial DNA; Phylogeny